Aesthetic Surgical Approach for Bone Dehiscence Treatment by Means of Single Implant and Interdental Tissue Regeneration: A Case Report with Five Years of Follow-Up - Giorgio Lombardo; Jacopo Pighi; Giovanni Corrocher; Anna Mascellaro; Jeffrey Lehrberg; Mauro Marincola; Pier Francesco Nocini (Case Reports in Dentistry)
The replacement of single anterior teeth by means of endosseous implants implies the achievement of success in restoring both aesthetic and function. However, the presence of wide endoperiodontal lesions can lead to horizontal hard and soft tissues defects after tooth extraction, making it impossible to correctly place an implant in the compromised alveolar socket. Vertical augmentation procedures have been proposed to solve these clinical situations, but the amount of new regenerated bone is still not predictable. Furthermore, bone augmentation can be complicated by the presence of adjacent teeth, especially if they bring with them periodontal defects. Therefore, it is used to restore periodontal health of adjacent teeth before making any augmentation procedures and to wait a certain healing period before placing an implant in vertically augmented sites, otherwise risking to obtain a nonsatisfactory aesthetic result. All of these procedures, however, lead to an expansion of treatment time which should affect patient compliance. For this reason, this case report suggests a surgical technique to perform vertical bone augmentation at a single gap left by a central upper incisor while placing an implant and simultaneously to regenerate the periodontal attachment of an adjacent lateral incisor, without compromising the aesthetic result.